Islam dan Ideologi dalam Pembangunan di Indonesia: Studi Terhadap Program Nawacita - bin Mawazi, Abd. Rahman; Hidayatulah, Rizki Pradana (Analisis: Jurnal Studi Keislaman, 2018)
The Islamic political movement in Indonesia still leaves the battle of discourse regarding the formalization of Islamic Shari'a as an ideology and Pancasila as the ideology adopted by the current state. This discourse battle is also often a stumbling block of government programs because the modernization carried out by the government often clashes with the values set by the community. This paper would like to see the correlation between Islam as an ideology and the development program in the cabinet of Joko Widodo and Jusuf Kalla. In its program, infrastructure development is so dominant in the hope of being able to support the national economic movement. In an Islamic perspective, the concept of modernization chosen by the government is part of the program of maslahat al-ummah or the interests of the people and is already a government obligation to fulfill. However, the practice that occurs in Indonesia is as it is known in the deconfentialization theory, that is, the general values of religious teachings are the main values in the state but the state is not based on religion. In this case, the modernization practices applied by the cabinet of Joko Widodo and Jusuf Kalla were more likely to be secularized. This pattern is still similar to that applied by the previous government. In an effort to accommodate the ideological interests of Islamic groups, the Jokowi-JK government still cannot make an appropriate compromise. The efforts made by the government are merely proposing jargon, namely the Mental Revolution.